PEMANFAATAN MEDIA PADA PEMBELAJARAN IPA SISWA KELAS VIII SMPN 3 TELUK KUANTAN - Nur Azizah; Yuslim Fauziah; Riki Apriyandi Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to find out the use of media in science learning for class VIII students of SMPN 3 Teluk Kuantan. This research was conducted at SMPN 3 Teluk Kuantan, Kuantan Tengah District, Kuantan Singingi Regency in March-April 2022. This type of research is classified as descriptive research using a qualitative approach. Data collection instruments consist of observation sheets, questionnaires, interview sheets, and documentation. The research sample was taken using a purposive sampling technique. Data and data sources were obtained from observations in the laboratory, questionnaires were given to 2 science teachers and 30 class VIII students. The results showed that the use of media based on the results of the teacher's questionnaire was 78%, and based on the student's questionnaire, namely 73%, included in the good category. Based on the research results, it can be concluded that the use of science learning media is included in the good category, and in accordance with the subject matter and learning objectives.Key Words: utilization, media, science learning